Drivers of compositional turnover in narrow‐ranged and widespread dragonflies and damselflies in Africa - Basel, Ashleigh Megan; Simaika, John P.; Samways, Michael J.; Midgley, Guy F.; Latombe, Guillaume; MacFadyen, Sandra; Hui, Cang (Wiley, 2024)
We aim to explore what processes dominate community assembly of dragonflies (Odonata: Anisoptera) and damselflies (Odonata: Zygoptera) by differentiating the environmental and geographical drivers behind compositional turnover of narrow‐ranged versus widespread species. In this way, we further aim to describe patterns of species incidence and compositional turnover to expand upon the body of knowledge related to understanding biodiversity patterns and processes. We explored species turnover of dragonflies and damselflies separately, using zeta diversity to measure compositional turnover among multiple assemblages. Narrow‐ranged and widespread species within each suborder showed similar drivers. Specifically, both narrow‐ranged and widespread dragonflies show rapid turnover with small shifts in annual mean temperature, temperature seasonality and annual precipitation, whereas for damselflies, the major driver for turnover is distance between sites followed by climatic variables. Our results therefore show that odonate turnover is largely driven by climate, although the limited dispersal capabilities of damselflies also influences community assembly. Climate change could cause major changes in composition of odonates, presenting a challenge for conservation planning in Africa as species assemblages that were previously conserved may no longer be protected if their ranges shift outside protected areas. For damselflies, adaptation is a major concern, and with their limited dispersal capabilities and climate sensitivity, they may not be able to migrate effectively in response to changing climate conditions. The underlying assembly processes do not differ considerably for narrow‐ranged and widespread species within each suborder, suggesting that conservation planning tailored to each suborder may be sufficient in Africa.